KONSEP WELLFARE STATE DI INDONEISA - Winda Roselina Effendi (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan ilmu Politik Universitas Riau Kep, 2017)
Walfare State concept born in the era of the 20th century as a correction of the development of the concept of the country as night watchman, the phenomenon of economic capitalism that gradually leads to lameness in the distribution of sources of prosperity. In the Walfare State concept, the state is required to extend its responsibility to the socio-economic problems facing the people. The functions of the state also include activities that were previously beyond the scope of state functions, such as extending the provision of social services to individuals and families in specific matters, such as social security. The role of the state can not be separated with Welfare State because the state that plays a role in managing the economy which includes the responsibility of the state to ensure the availability of basic welfare services in certain levels. Welfare State does not reject the existence of a capitalist market economy system but believes that there are elements in the public order that are more important than market objectives and can only be achieved by controlling and limiting the operation of such market mechanisms.Keywords: walfare state, country, economic systemKonsep Walfare State yang lahir di era abad ke-20 sebagai koreksi berkembangnya konsep negara sebagai penjaga malam, gejala kapitalisme perekonomian yang secara perlahan-lahan menyebabkan terjadinya kepincangan dalam pembagian sumber-sumber kemakmuran bersarma. Dalam konsep Walfare State, negara dituntut untuk memperluas tanggung jawabnya kepada masalah-masalah sosial ekonomi yang dihadapi rakyat. Fungsi negara juga meliputi kegiatan-kegiatan yang sebelumnya berada diluar jangkauan fungsi negara, seperti memperluas ketentuan pelayanan sosial kepada individu dan keluarga dalam hal-hal khusus, seperti social security, kesehatan. Peran negara tidak bisa dipisahkan dengan Welfare State karena negara yang berperan dalam mengelola perekonomian yang yang di dalamnya mencakup tanggung jawab negara untuk menjamin ketersediaan pelayanan kesejahteraan dasar dalam tingkat tertentu. Welfare State tidak menolak keberadaan sistem ekonomi pasar kapitalis tetapi meyakini bahwa ada elemen-elemen dalam tatanan masyarakat yang lebih penting dari tujuan-tujuan pasar dan hanya dapat dicapai dengan mengendalikan dan membatasi bekerjanya mekanisme pasar tersebut. Kata Kunci: walfare state, negara,sistem ekonomi